The role of tourism in island economic growth and resilience: A panel analysis for the European Mediterranean countries (2000–2015). Issue 7 (11th November 2019) - Mazzola, Fabio; Pizzuto, Pietro; Ruggieri, Giovanni
Abstract : Purpose: The purpose of this paper is to verifying the economic resilience of islands and, in particular, the role of the tourism sector in the reaction to the most recent economic crisis. The analysis concerns insular contexts, such as the greater island regions in the Mediterranean basin. Design/methodology/approach: Static and dynamic panel data techniques are used for a sample of 13 island economies over a period of 16 years. Findings: Results show that the growth factors for regional islands are similar to the ones usually considered for other regions, but the tourism-led growth hypothesis is highly supported. Tourism demand more than supply plays a role together with accessibility. The crisis has reduced the importance of tourism supply, while tourism demand and accessibility have remained crucial for growth together with other traditional engines of growth. Originality/value: To the best of authors' knowledge, none of the current works has considered territorial determinants and tourism indicators inside the same framework analyzing growth in island economies by considering the changes occurred during the crisis explicitly.